Pengaruh Budaya Organisasi Dan Stres Kerja Terhadap Kinerja Karyawan Pada PT. Kawasan Berikat Nusantara (Persero) Jakarta Utara - Muksin Kalbadri; Karyaningsing Karyaningsing (COSTING : Journal of Economic, Business and Accounting, 2021)
This study aims to determine how much the relationship between Organizational Culture and Work Stress on Employee Performance at Pt. Nusantara Bonded Zone (Persero) North Jakarta. The purpose and research is to obtain a systematic description of organizational culture and stress as independent variables and performance as included variables, verificatively aims to test the hypothesis with statistical calculations. In this study using descriptive and verification research methods. The population in this study were employees of PT Kawasan Berikat Nusantara (Persero) which was planned to be 104 people divided into several divisions and positions. The sample used in this study is saturated sample, saturated sample is also often interpreted as the maximum sample, because added no matter how much will not change the population representation. In the research sample, all employees who work at PT Kawasan Berikat Nusantara (Persero). The types of data used by researchers in research on the influence of organizational culture and work stress on performance are primary and secondary data. Data collection techniques conducted by researchers are, questionnaire interviews, observation. Berikat Nusantara (Persero). Organizational culture contributes partially by 15.6% to performance. Meanwhile, work stress contributed partially by 9.7% to performance. Because 15.6% is greater than 9.7%, it can be stated that the Organizational Culture variable contributes more to performance than the Work Stress variable. The effect of the simultaneous influence of Organizational Culture and Work Stress on Employee Performance at PT Kawasan Berikat Nusantara (Persero) is 25.3%. Keywords: Organizational Culture, Work Stress, Employee Performance